Reticular substance - Trelles, J. O. (1959)
In addressing the issue of the reticular substance, nothing better than to repeat the phrase HARVEY CUSHING, who opens his book on the hypothalamus, "there is nothing really new and exciting in the sun, which is new to us seems to be something new something old "and JEAN LHERMITTE adds," that doubted the accuracy of this reflection, which is nothing more than an old idea, we would advise you to take the actual evolution of neurology ". And we paraphrase the master, we reopened the debate on the complex problem and the multiple theories on the reticular formation. What we bring is not scientific novelty, it is only old posts of topics on the agenda under new points of view condensate hypothesis can perhaps convince today, but did not resist the relentless criticism of the evolution of thought over time.